The effectiveness of the Electronic archiving system at the Documentation and Administrative Communication Center at Umm Al-Qura University: A case study - Al-Qathami, Maram Mohammed (Journal of Humanities & Social Sciences, 2021)
The study aimed at identifying the electronic archiving system used in the Documentation and Administrative Communication Center at Umm Al-Qura University. It is a laser fiche system for document management and workflow solutions, which is the main goal of the study; revealing the reality of the use of the electronic archiving system in the center, its effectiveness in meeting its needs, the reasons for its selection of the system, its most important characteristics, and the identification of the methods used for the security and safety of documents. The study also reviews advantages and disadvantages of the used technique in order to conclude a number of results and recommendations which contribute to improvement and development of the system at the documentation and administrative communication center. This is because it is an essential pillar for achieving progress and development in conducting and archiving transactions in addition to raising the level of the university among other universities. Methodology of The Study: This study relied on the descriptive approach using the case study method as it fits with the subject of the study. Data was collected through an interview form directed to the Director of the Documentation and Administrative Communications Center. In addition, preparing a questionnaire including a set of multiple-choice questions sent via e-mail and communication to be completed by phone calls. Results of The Study: The study concluded a number of results, the most important of which are: that the electronic archiving system; Laser Fiche was able to achieve many advantages for the Documentation and Administrative Communication Center at Umm Al-Qura University. It also achieved the desired goals of its application. The study also proved the efficiency of the system in addition to the presence of Work Flow "Masirat" in order for the system to do some points that help the user. Recommendations: The researcher concluded a set of recommendations, the most important of which are: the necessity of continuous updating of the system and activating all its applications, and its developing to solve problems that were monitored through the results.